DAUR PATOLOGIS TEGAKAN HUTAN TANAMAN Acacia mangium Willd. - Simon Taka Nuhamara; Soetrisno Hadi; Endang Suhendang; Maggy T Suhartono; Wasrin Syafii; Achmad Achmad (Research Center for Biology-Indonesian Institute of Sciences, 2008)
Heart rot on Acacia mangium Willd. forest stand is critical especially for mechanical or construction wood based purposes. Failure on understanding the nature and the way it get established into the tree stem may cause high economic consequences.Anticipating such a worse condition, studies on cull factor in relation to age was initiated. Eventually the study is aimed at healthy cutting cycles of the clear and purposely stand establishment. The study had been carried out at BKPH Parung Panjang, KPH Bogor. Following the cull factor measurement technique combined with the pathological rotation estimation procedures, it was found that the healthy volume was 0.0623 m and the cull factor was 31.25 %.The figures were at the age of nine years. Therefore, the pathological rotation cycle for the A. mangium stand in the area could be fitted at eight years, as being adopted so far.This is true, when the plantation is established for the production of wood, provided that the tending operation is optimal. Applying the United States Department of Agriculture (USDA) Forest Health Monitoring (FHM) indices, the general performance of the A. mangium forest stand in Parung Panjang is found to be in healthy criteria. The damage indices for all stand ages investigated varied from 2.77 (lowest) to 5.16 (highest) as compared to the 21.18 value, the possible highest FHM tree index.